1997
DOI: 10.1007/bf01808821
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in severely head injured adult patients with epidural haematoma's

Abstract: A medline search back to 1975 was undertaken to identify relevant papers published on epidural haematomas. The search was restricted, whenever possible, to adult age and to comatose patients. Forty four relevant reports were identified. Only 4 papers reported results on multivariate analysis. In terms of prognosis, the following parameters were found to be significant: age, time from injury to treatment, immediate coma or lucid interval, presence of pupillary abnormalities, GCS/motor score on admission. CT fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…A possible explanation for this difference might be the fact that these studies included only patients where EDH was the predominant injury whereas in our study most patients with EDH had additional intracranial lesions that might have influenced outcome. Another German study (Regel et al) [10] stated that mortality of EDH was commonly 0-40%, and Servadei [11], summarizing other studies from various authors, reported a rate between 9% and 59%. All of these studies deal with operatively and nonoperatively treated cases.…”
Section: Discussionmentioning
confidence: 97%
“…A possible explanation for this difference might be the fact that these studies included only patients where EDH was the predominant injury whereas in our study most patients with EDH had additional intracranial lesions that might have influenced outcome. Another German study (Regel et al) [10] stated that mortality of EDH was commonly 0-40%, and Servadei [11], summarizing other studies from various authors, reported a rate between 9% and 59%. All of these studies deal with operatively and nonoperatively treated cases.…”
Section: Discussionmentioning
confidence: 97%
“…It helped us to diagnose EDH in all 36 patients in our series. Older studies showed the role of cerebral angiography in diagnosing EDH (4,21). However, CT scan become the investigation of choice to diagnose the volume and location of EDH, associated injuries and midline shift etc.…”
Section: █ Discussionmentioning
confidence: 99%
“…(16). It has been reported that the mortality rate was between 29 and 33% in the pre-CT era and between 9 and 12% in the post-CT era (4,21). Persistent headache and vomiting are important indications for a CT scan after head trauma (16).…”
Section: █ Discussionmentioning
confidence: 99%
“…The most important neurosurgical problem with an extra-axial hematoma is the occurrence of a brain herniation due to rapid enlargement of the hematoma [7,8]. Brain herniation is a catastrophic factor and can lead to mortality via brainstem ischemia [9].…”
Section: Discussionmentioning
confidence: 99%